Application of Green Chemistry Principle in Synthesis of Phenytoin and Its Biogical Evaluation as Anticonvulsant Agents - Abhijit Kadam; Sampada Jangam; Rajesh Oswal (E-Journal of Chemistry, 2011)
Phenytoin (5,5'-dipenylimidazolidine-2,4-dione) is the prime example of anticonvulsant agent. According to reported procedure, it is synthesized by condensation of benzil and urea in presence of base (30% w/v NaOH) using ethanol as solvent which itself acts as CNS stimulant. Removal of solvent after synthesis is most difficult and non-assured process. In case of phenytoin transformation in polymorphism plays an important role when solvent other than water is used. About 30% extra cost is calculated if solvent other than water is used. Therefore by application of green chemistry principle phenytoin was synthesized by condensation of benzil and urea in presence of base (30% NaOH) and water as green solvent. This compound was characterized on the basis of its spectral (IR, 1H NMR) data and evaluated for anticonvulsant activity using MES induced and PTZ induced seizure models in Swiss albino mice. Significant anticonvulsant activity was found by using 25 mg/kg and 50 mg/kg of phenytoin compared with standard phenytoin at 25 mg/kg dose.